2011
DOI: 10.1002/0471140864.ps1208s66
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Analysis of Proteins Modified by O‐Linked N‐Acetylglucosamine

Abstract: O-GlcNAc is a common post-translational modification of nuclear, mitochondrial and cytoplasmic proteins, that is implicated in the etiology of type II diabetes and Alzheimer’s disease, as well as cardioprotection. This unit covers simple and comprehensive techniques for identifying proteins modified by O-GlcNAc, studying the enzymes that add and remove O-GlcNAc, and mapping O-GlcNAc modification sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 86 publications
(82 reference statements)
1
33
0
Order By: Relevance
“…Using these methods, many S. elongatus proteins were detected, but wild-type and mutant samples showed the same labeling patterns (data not shown). Several antibodies are currently available to detect the O-GlcNAc modification (18). Western blotting using these antibodies detected many proteins but did not reveal differences between the mutant and wild type (data not shown).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Using these methods, many S. elongatus proteins were detected, but wild-type and mutant samples showed the same labeling patterns (data not shown). Several antibodies are currently available to detect the O-GlcNAc modification (18). Western blotting using these antibodies detected many proteins but did not reveal differences between the mutant and wild type (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…Several methods are currently used to identify O-GlcNAcylated proteins, including transfer of labeled galactose to a known terminal O-GlcNAc, the use of antibodies against the OGlcNAc modification, and chemi-enzymatic methods (18). The GalT assay uses the enzyme ␤-1,4-galactosyl transferase, which adds a labeled galactose to proteins with glycosylations terminating in GlcNAc.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of PilA was performed as previously described (2), while detection of HmpD followed the same protocol (using a 1:10,000 dilution of primary antibody), with the exception that a 10% SDS-PAGE gel was used. Detection of O-GlcNAcylated proteins using the anti-OGlcNAc monoclonal antibody CTD110.6 (Enzo Life Sciences, Inc.) in conjunction with goat anti-mouse IgG-horseradish-conjugated peroxidase (HRP) (sc2005; Santa Cruz Biotechnology), or biotinylated succinylated wheat germ agglutinin (sWGA) (Vector Laboratories) in conjunction with the avidin-HRP conjugate Vectastain ABC reagent, was performed as previously described (2,41). Detection and quantification of soluble hormogonium polysaccharide in the culture medium by lectin blotting with biotinylated Ulex europaeus agglutinin (UEA) were performed as previously described (3).…”
Section: Methodsmentioning
confidence: 99%
“…These antibodies fall into two classes: those that can be considered pan-specific and others that are site specific (Zachara et al 2011c). The two most commonly used pan-specific antibodies for detecting O-GlcNAc-modified proteins are CTD110.6 , a mouse IgM antibody raised against the C-terminus of RNA Pol II, and RL2 (Snow et al 1987), a mouse IgG antibody raised against O-GlcNAc-modified components of the nuclear pore complex.…”
Section: Immunopurification With Antibodies and Lectinsmentioning
confidence: 99%
“…As such, proteins that interact with O-GlcNAc-modified proteins are also identified, and in most cases O-GlcNAc-modified peptides are suppressed in the MS making O-GlcNAc modification sites difficult to map. Nonetheless, a number of studies have been performed highlighting proteins that are potentially OGlcNAc-modified in response to cellular stress and tissue injury Teo et al 2010;Zachara et al 2011c), and the O-GlcNAcylation status of a number of proteins has been confirmed by independent techniques (Table 1). One recent study used 1F5.D6(14), 18B10.C7(3), and 9D1.E3(10) to immunoprecipitate O-GlcNAc-modified proteins followed by large-scale shotgun proteomics to identify more than 200 differentially expressed glycoproteins from HEK293 cells and rat livers responding to trauma hemorrhage and resuscitation (Teo et al 2010).…”
Section: Immunopurification With Antibodies and Lectinsmentioning
confidence: 99%